Supportive work environment for people with Down syndrome in Malaysia: a cross-sectional study - Rahman, Md Mizanur; Ting, Chuong Hock; Safii, Razitasham; Saimon, Rosalia; Chen, Yoke Yong; Puteh, Sharifa Ezat Wan; Adenan, Abg Safuan (International Journal of Public Health Science (IJPHS), 2025)
Understanding organizational culture, knowledge of employment rights, and positive attitudes towards people with disabilities is crucial for creating inclusive workplaces. This Malaysian study compared the perspectives of employers, employees, and community members with disabilities using a cross-sectional design and convenience sampling of 595 respondents. Data on demographics, organizational culture, legislative knowledge, and attitudes were collected via a validated survey and analyzed using descriptive statistics, one-way analysis of variance (ANOVA), and multiple linear regression in JAMOVI and SPSS, with a p-value<.05 indicating significance. The study found a moderately supportive organizational culture for employing people with disabilities, with the highest scores in supportive work environments and inclusive culture. Employers and employees perceived greater top management commitment and inclusivity than community members with Down syndrome. Legislative knowledge and positive attitudes significantly shaped perceptions of a supportive and inclusive workplace. Muslim participants reported greater support and disability-accommodating human resource (HR) practices than those of other religions. The findings underscore the need for targeted training and awareness programs on disability rights to enhance inclusivity among all stakeholders in Malaysia.